Bhutan Policy Notes : Attracting Foreign Direct Investment - World Bank (World Bank, Washington, DC, 2019)
In recent years, Bhutan has been revising its policy and increasing its efforts to attract FDI inflows. The existing policy regime governing FDI inflows is spelt out in the 2010 FDI Policy (amended in 2014). Despite the policy there are several reasons why Bhutan is not getting significant FDI inflows.